2022
DOI: 10.1002/edn3.333
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospherebacterial communities differ among traditional maize landraces

Abstract: Microbes are associated with nearly all surfaces of plants and are even present within multiple cell types (Compant et al., 2019). The rhizosphere is arguably the most important sites for plant-microbe interactions, with the fungi and bacteria within the rhizosphere directly linked to host vitality. Consequently, understanding the regulation of the rhizosphere microbiome is of considerable importance,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Inter-species variation in the host plant genome has been found to have a relatively small effect on the associated microbial communities compared with other factors such as environmental variation [6,50,51,56,57]. In this work, we found that the rhizosphere bacterial communities of Eglouvis samples were divergent compared to Demetra regarding the amounts of participating N 2 -fixing bacteria.…”
Section: Microbial Diversitymentioning
confidence: 59%
See 1 more Smart Citation
“…Inter-species variation in the host plant genome has been found to have a relatively small effect on the associated microbial communities compared with other factors such as environmental variation [6,50,51,56,57]. In this work, we found that the rhizosphere bacterial communities of Eglouvis samples were divergent compared to Demetra regarding the amounts of participating N 2 -fixing bacteria.…”
Section: Microbial Diversitymentioning
confidence: 59%
“…Nowadays, mounting evidence from research indicates that the plant genome has a central and dynamic role in shaping the composition of the microbiome [5,6]. Awad and coworkers have shown that the phyllosphere microbiome in grapevine cultivars is governed by the cultivar genotype in a collection of grapevine cultivars grown in the same orchard [7], thus, demonstrating that the plant genotype is key player of the above-ground plant microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus not surprising that these specialized metabolites have been under positive selection during crop domestication. [40,203,204] By shaping the plant interactions with other living organisms, benzoxazinoids shape the evolution of trophic interactions and ecosystem functioning. [192,193,[205][206][207] Harnessing their power in modulating the plant physiology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of studies have documented general effects, often as associations, of host genetic background on the microbiota in various experimental and ecological contexts including at the species level (Sylvain et al., 2022), inter‐individual level (Boutin et al., 2014), or population level (Kurilshikov et al., 2021; Lopera‐Maya et al., 2022; Small et al., 2023; Smith et al., 2015). Here, host‐associated microbiota is defined as all the microbes and their abundances that can preside within and on the host at any given point in time (Lund et al., 2022; Velasquez et al., 2023). Thereby the host‐genetic factors create a restraint on the microbiota community composition.…”
Section: Introductionmentioning
confidence: 99%